The Relationship between Parent-Offspring Communication and the School Adaptation of Leftover Children in Overseas Countries: The Mediating Role of Companionship and the Moderating Role of a Sense of Safety - Huilan Zhang; Bingwei Shen; Chunkao Deng; Xiaojun LYu (Behavioral Sciences, 2023)
Background: In the diasporic eastern coastal region of China, leftover children are a unique group of children; their social adaptation challenges are more prominent due to transnational separation from parents. This study explores the relationship between parent-offspring communication and school adaptation among leftover children. Methods: We administered questionnaires to 957 children from six schools in June and December of 2022. All students in the sample were randomly selected from within the classrooms. In total, 561 (47.95% female, mean age = 12.84, SD = 0.95) of them were leftover children. Self-report questionnaires on communication with their parents, school adaptation, companionship, and feelings of safety were used in this investigation We subsequently used SPSS software and the PROCESS plugin to analyze the relationships between variables. Results: A significant and positive relationship was found between parent-offspring communication and school adaptation in leftover children. Companionship mediated this effect. Additionally, the impact of parent-offspring communication on companionship was moderated by a sense of safety. Conclusions: The study concluded that parent-offspring communication, school adaptation, companionship, and a sense of safety were all positively correlated. In addition, companionship partially mediated the relationship between parent-offspring communication and school adaptation. Moreover, a sense of safety played a moderating role. These conclusions can provide empirical support for improving the school adaptation of leftover children.